1995
DOI: 10.1002/jhet.5570320357
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling, NMR spectroscopy, and conformational analysis of 3′,4′‐anhydrovinblastine

Abstract: The assignment of the proton spectrum of 3′,4′‐anhydrovinblastine is reported. Assignments are made for several protons for which only approximate assignments were available previously. Homonuclear TOCSY and ROESY spectra were utilized in conjunction with HMQC and HMBC spectra in making the assignment. Correlations in the ROESY spectrum suggested a preferred conformation of the cleavamine (upper) portion of 3′,4′‐anhydrovinblastine in which the 21‐methyl of the 20/21 ethyl group of the vindo‐line (lower) porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…This finding indicated that the cleavamine unit could behave differently (both conformationally as well as chemically) in VLB-type diindoles and in monomers, thus any conclusions extrapolated from monomeric building blocks should be handled with care. Andrews et al [85] confirmed this "natural-y" conformation for the velbanamine half of AVLB. They completed the assignments missing from the previous work [84] due to broadening of the resonances belonging to the nine-membered ring.…”
Section: Conformational Aspects Of Vlb Analoguesmentioning
confidence: 67%
See 1 more Smart Citation
“…This finding indicated that the cleavamine unit could behave differently (both conformationally as well as chemically) in VLB-type diindoles and in monomers, thus any conclusions extrapolated from monomeric building blocks should be handled with care. Andrews et al [85] confirmed this "natural-y" conformation for the velbanamine half of AVLB. They completed the assignments missing from the previous work [84] due to broadening of the resonances belonging to the nine-membered ring.…”
Section: Conformational Aspects Of Vlb Analoguesmentioning
confidence: 67%
“…Continuing with these investigations, an analysis of the solution behaviour of AVLB and its borane complex was conducted by Szántay et al [84] and by Andrews and co-workers [85]. In the former paper, an NMR investigation including the use of 1 H 1 H NOE measurements in the presence of 11 B decoupling were performed together with COSY and 13 C 1 H heterocorrelation methods for AVLB and its borane complex using a 400 MHz spectrometer.…”
Section: Conformational Aspects Of Vlb Analoguesmentioning
confidence: 98%
“…Computation of random or pseudorandom numbers causes the accuracy of calculation particularly for unfeasible or impossible to estimate an exact data with a deterministic algorithm [33]. It doesn't always need random numbers to apply deterministic, pseudo-random sequences, making it easy to test and re-run simulations [34]. In MC methods, a sequence of points in the phase space is produced from an initial geometry by adding a random "kick" to the coordinates of a randomly chosen atom or molecule.…”
Section: Methodsmentioning
confidence: 99%
“…It doesn't always need random numbers to use deterministic, pseudo-random sequences, making it easy to test and re-run simulations [49]. In Monte Carlo (MC) methods, a sequence of points in phase space is generated from an initial geometry by adding a random "kick" to the coordinates of a randomly chosen particle (atom or molecule).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The new configuration is accepted if the energy decreases and with a probability of e−∆E/kT if the energy increases. This Metropolis procedure ensures that the configurations in the ensemble obey a Boltzmann distribution, and the possibility of accepting higher energy configurations allows MC methods to climb uphill and escape from a local minimum [49].…”
Section: Theoretical Backgroundmentioning
confidence: 99%